2022
DOI: 10.17073/0368-0797-2022-9-637-643
|View full text |Cite
|
Sign up to set email alerts
|

Properties of coatings obtained by supersonic electric arc metallization with aerosol fluxing

Abstract: The method of electric arc metallization has both undeniable advantages and some disadvantages. For example, there is a burnout of alloying elements and a high content of oxides in the applied coating. Aerosol fluxing during metallization can solve this problem and neutralize the negative oxidative effect of interaction of the applied metal with air oxygen. This article discusses an effective method to improve physical and mechanical properties of an electrometallization coating using aerosol fluxing. The esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The shape of the flattened metal particles allows us to conclude that at the moment of impact they were in a plastic state, in which they are easily deformed. In [15], the mechanism of coating formation during electric arc metallization was shown and it was found that large metal particles reach the surface mainly in the liquid state, while smaller ones in the plastic and even solid state. Liquid metal wets the surface and fills in irregularities, while colder (semi-liquid) metal particles are deformed upon impact and mixed with hotter ones, forming a single coating layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the flattened metal particles allows us to conclude that at the moment of impact they were in a plastic state, in which they are easily deformed. In [15], the mechanism of coating formation during electric arc metallization was shown and it was found that large metal particles reach the surface mainly in the liquid state, while smaller ones in the plastic and even solid state. Liquid metal wets the surface and fills in irregularities, while colder (semi-liquid) metal particles are deformed upon impact and mixed with hotter ones, forming a single coating layer.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting coatings are usually dense, uniform and have good adhesion to the substrate. They also have good resistance to wear, corrosion and high temperatures [3][4][5]. Coatings can be applied to improve the surface properties of a material for a variety of applications, including aerospace, automotive, and industrial applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%